Integrating physiology, genetics, and transcriptome to decipher a new thermo-sensitive and light-sensitive virescent leaf gene mutant in cucumber - Zhang, Zhipeng; Wang, Jinyao; Xing, Guoming; Li, Meilan; Li, Sen (Frontiers in Plant Science, 2022)
Chloroplasts are the material basis of photosynthesis, and temperature and light severely affect chloroplast development and thus influence photosynthetic efficiency. This study identified a spontaneous virescent leaf mutant, SC311Y, whose cotyledons and true leaves were yellow and gradually turned green. However, temperature and light affected the process of turning green. In addition, this mutant (except at the seedling stage) had ruffled leaves with white stripes, sterile males, and poorly fertile female flowers. Genetic characteristics analysis revealed that the recessive gene controlled the virescent leaf. Two F2 populations mapped v-3 to the interval of 33.54-35.66 Mb on chromosome 3. In this interval, BSA-Seq, RNA-Seq and cDNA sequence analyses revealed only one nonsynonymous mutation in the Csa3G042730 gene, which encoded the RNA exosome supercomplex subunit resurrection1 (RST1). Csa3G042730 was predicted to be the candidate gene controlling the virescent leaf, and the candidate gene may regulate chloroplast development by regulating plastid division2 (PDV2). A transcriptome analysis showed that different factors caused the reduced chlorophyll and carotenoid content in the mutants. To our knowledge, this study is the first report of map-based cloning related to virescent leaf, male-sterile, and chloroplast RNA regulation in cucumber. The results could accelerate the study of the RNA exosome supercomplex for the dynamic regulation of chloroplast RNA.